2015
DOI: 10.1002/art.39306
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Factor Is Associated With the Distribution of Hand Joint Destruction in Rheumatoid Arthritis

Abstract: Objective Rheumatoid arthritis (RA) is a chronic disease leading to joint destruction. Although many studies have addressed factors potentially correlated with the speed of joint destruction, less attention has been paid to the distribution of joint destruction in patients with RA. In this study, destruction of the hand bones in patients with RA was classified into 2 anatomic subgroups, the fingers and the non‐fingers, with the aim of analyzing which factors are associated with destruction of the finger joints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…To perform functional analysis, we selected rs11125908 in an intron of COMMD1 which was 75bp from and in strong LD with rs10205855 (r 2 =0.98, Figure S3A). In Japanese RA patients (Terao et al, 2015), the minor allele G at rs11125908, showing significant cis eQTL association with increased COMMD1 expression (Figure 3B), was concurrently associated with lower bone erosions of hand joints (Figure 3C). Furthermore, rs11125908 G alleles demonstrated a strong suppressive association with finger joint destruction, independently of rheumatoid factor (RF) positivity (Figure S3B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To perform functional analysis, we selected rs11125908 in an intron of COMMD1 which was 75bp from and in strong LD with rs10205855 (r 2 =0.98, Figure S3A). In Japanese RA patients (Terao et al, 2015), the minor allele G at rs11125908, showing significant cis eQTL association with increased COMMD1 expression (Figure 3B), was concurrently associated with lower bone erosions of hand joints (Figure 3C). Furthermore, rs11125908 G alleles demonstrated a strong suppressive association with finger joint destruction, independently of rheumatoid factor (RF) positivity (Figure S3B).…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed 340 patients with RA from the Kyoto University Rheumatoid Arthritis Management Alliance (KURAMA) cohort at Kyoto University, as previously described (Terao et al, 2015). DNA was available from 176 RA patients among the 340 patients in the Kyoto University Rheumatoid Arthritis Management Alliance (KURAMA) cohort.…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] RA could cause joint swelling, pain, loss of function and stiffness and tremendously impact on health and quality of life of patients. [5][6][7][8] The prevalence of RA is about 3 times higher in females than males. [9][10][11] The pathogenesis of RA is complex and involves an intricate interplay between host factors (eg genetic susceptibilities, aberrant immune response, abnormal metabolic enzymes and sex hormones) and environmental triggers (eg bacterial or viral infection).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, patients positive for both RF and ACPAs seem to exhibit more severe erosive bone damage compared with those who are positive for only one of the autoantibodies [30], suggesting that the combination of these autoantibodies is strongly linked to a worse clinical disease course of RA [31]. Moreover, we recently reported that RF and ACPAs positivity contribute to joint destruction of particular joints in patients with RA [32,33]. In this study, we found that the sLOX-1 level was markedly higher in patients with the combined presence of RF and ACPAs in the non-remission group compared with those in the remission group ( Figure 1C).…”
Section: Discussionmentioning
confidence: 91%